A case for scholarly making in the library: Makerspaces, innovation labs, and the evolution of scholarly communications. Issue 2 (10th November 2021) - Fletcher, Curtis
Abstract: This article leverages an innovative maker program at the University of Southern California Libraries to explore how academic libraries are uniquely positioned to partner with student researchers to unite experimental modes of digital scholarly communication with a maker ethos. Focusing on one instance of the program, the result of which was a novel, research-driven annotated VR experience of a terraformed Mars, the author argues that academic libraries, and innovation labs within those libraries, can foster experimental scholarly communications, with students and others, by advancing key partnerships across campus and by providing a potent mixture of space, technology, and in-house digital literacy skills.